Duplex qPCR for detecting and differentiating porcine epidemic diarrhea virus GI and GII subtypes - Wang, Bin; Han, Wang; Wu, Di; Jing, Yue; Ma, Li; Jiang, Feiyang; Ji, Shusen; Bai, Lianmei; Yu, Xiuju; Hou, Wei; Wang, Shouyu; Wang, Haidong (Frontiers in Microbiology, 2025)
IntroductionPorcine epidemic diarrhea virus (PEDV) is a pathogen that causes a highly contagious intestinal disease in pigs, which causes significant economic losses to the pig industry worldwide. PCR is the most commonly used technique for PEDV diagnosis in practical clinics, however, reported works still suffer from shortcomings, for example, most of them cannot differentiate GI and GII subtypes, they suffer from low sensitivity, and some primer sequences are no longer able to match the mutant strains.MethodsTo address these issues, we conducted a comprehensive analysis by comparing the sequences of the PEDV S protein in the existing NCBI database with a recently isolated epidemic strain of PEDV, named SX0818-2022, of subtype GIIa from Shanxi, China. The conserved sequences of GI and GII subtypes were retrieved to design the primers and probe. Leveraging this information, we developed a TaqMan probe-based quantitative real-time PCR (qPCR) assay that is uniquely tailored to detect both PEDV GI and GII subtypes.ResultsAdditionally, this qPCR can identify PEDV GI and GII subtypes with high sensitivities of 90 copies/μL and 40 copies/μL, respectively (refers to the number of copies of the DNA target per microliter of template in the reaction system), much higher than the previously reported works and especially suitable for early diagnosis and prevention. Besides, excellent specificity and repeatability of the duplex qPCR were verified, thus supporting its potential applications in practical clinics.DiscussionTherefore, this work presents a promising tool for PEDV diagnosis, prevention, and control.